Anterior Cingulate Cortex Activity During Rest Is Related to Alterations in Pain Perception in Aging - Terrasa, Juan L.; Montoya, Pedro; Sitges, Carolina; van der Meulen, Marian; Anton, Fernand; González-Roldán, Ana M. (Frontiers in Aging Neuroscience, 2021)
Alterations in the affective component of pain perception are related to the development of chronic pain and may contribute to the increased vulnerability to pain observed in aging. The present study analyzed age-related changes in resting-state brain activity, and their possible relation to an increased pain perception in older adults. For this purpose, we compared EEG current source density and fMRI functional-connectivity at rest in older (n=20, 66,21±3,08 years) and younger adults (n=21, 20,71±2,30 years) and correlated it with pain intensity and unpleasantness ratings elicited by painful stimulation. We found an age-related increase in beta2 and beta3 activity in temporal, frontal and limbic areas, and a decrease in alpha activity in frontal areas. Moreover, older participants displayed increased functional connectivity in the anterior cingulate cortex (ACC) and the insula with precentral and postcentral gyrus. Finally, ACC beta 3 activity was positively correlated with pain intensity and unpleasantness ratings in older, and ACC-precentral/postcentral gyrus connectivity was positively correlated with unpleasantness ratings in older and younger participants. These results reveal that ACC resting-state hyperactivity may underlie the altered pain perception characteristic of aging, and therefore, could be considered as a biomarker of the predisposition to develop chronic pain in the older population.